Music festival supervisor leadership style and organizational citizenship behavior: the effects of employee and volunteer relationships and dependence on their leader - Sisson, A.D. (International Journal of Event and Festival Management, 2021)
Purpose: The relationship between leadership style and employee outcomes is well established. However, organizational management research lacks an understanding of the dyadic relationship between supervisors and employees and volunteers at music festivals. This study examines a mediation model in which leader–member exchange (LMX) affects leadership style and organizational citizenship behavior. Additionally, the study examines a moderating model in which dependence on the leader moderates relationships between leadership style and leader–member exchange. Design/methodology/approach: Confirmatory factor analysis, structural equation modeling and conditional process analysis were employed to test the model using data collected from 97 supervisors, volunteers and employees who worked at an annual large-scale music festival staged in Costa Rica. Findings: Results reveal that leadership style relates positively to LMX and organizational citizenship behavior (OCB). Simultaneously, the mediating effect of LMX and moderating effect of dependence on the leader was not significant on the leadership style and OCB. Research limitations/implications: Given the small sample size and accessibility to one music festival, caution should be taken in drawing causal conclusions from the results. Practical implications: The study contributes to the knowledge of event and festival management with recommendations for leadership training initiatives for supervisors and employees/volunteers. Originality/value: This study is among the first to examine the mediating role of LMX between leadership style and OCB, moderating the role of dependence on leadership style and LMX with music festival supervisors and employees/volunteers. © 2021, Emerald Publishing Limited.
Keywords: dept.rec; peer-reviewed